Up-regulation of the PI3K/AKT and RHO/RAC/PAK signalling pathways in CHK1 inhibitor resistant Eµ-Myc lymphoma cells. Issue 19 (14th October 2022) - Hunter, Jill E.; Campbell, Amy E.; Kerridge, Scott; Fraser, Callum; Hannaway, Nicola L.; Luli, Saimir; Ivanova, Iglika; Brownridge, Philip J.; Coxhead, Jonathan; Taylor, Leigh; Leary, Peter; Hasoon, Megan S. R.; et al.
Abstract : The development of resistance and the activation of bypass pathway signalling represents a major problem for the clinical application of protein kinase inhibitors. While investigating the effect of either a c-Rel deletion or RelA T505A phosphosite knockin on the Eµ-Myc mouse model of B-cell lymphoma, we discovered that both NF-κB subunit mutations resulted in CHK1 inhibitor resistance, arising from either loss or alteration of CHK1 activity, respectively. However, since Eµ-Myc lymphomas depend on CHK1 activity to cope with high levels of DNA replication stress and consequent genomic instability, it was not clear how these mutant NF-κB subunit lymphomas were able to survive. To understand these survival mechanisms and to identify potential compensatory bypass signalling pathways in these lymphomas, we applied a multi-omics strategy. With c-Rel −/− Eµ-Myc lymphomas we observed high levels of Phosphatidyl-inositol 3-kinase (PI3K) and AKT pathway activation. Moreover, treatment with the PI3K inhibitor Pictilisib (GDC-0941) selectively inhibited the growth of reimplanted c-Rel −/− and RelA T505A, but not wild type (WT) Eµ-Myc lymphomas. We also observed up-regulation of a RHO/RAC pathway gene expression signature in both Eµ-Myc NF-κB subunit mutation models. Further investigation demonstrated activation of the RHO/RAC effector p21-activated kinase (PAK) 2. Here, the PAK inhibitor, PF-3758309 successfully overcame resistance of RelA T505A but not WT lymphomas. These findings demonstrate that up-regulation of multiple bypass pathways occurs in CHK1 inhibitor resistant Eµ-Myc lymphomas. Consequently, drugs targeting these pathways could potentially be used as either second line or combinatorial therapies to aid the successful clinical application of CHK1 inhibitors.